Oxygen uptake and muscle deoxygenation kinetics during skating: Comparison between slide-board and treadmill skating - Piucco, T.; Soares, R.; Diefenthaeler, F.; Millet, G. Y.; Murias, J. M. (International Journal of Sports Physiology and Performance, 2018)
PURPOSE: To compare the oxygen-uptake (V.O2) kinetics during skating on a treadmill and skating on a slide board and to discuss potential mechanisms that might control the (V.O2) kinetics responses during skating.